Effect of oxygen supply strategy on nitrogen removal of biochar-based vertical subsurface flow constructed wetland: Intermittent aeration and tidal flow. (May 2019) - Li, Jing; Hu, Zhen; Li, Fazhan; Fan, Jinlin; Zhang, Jian; Li, Fengmin; Hu, Hongying
Abstract: Insufficient dissolved oxygen (DO) concentration is recognized as one of the major factors limiting efficient nitrogen removal in constructed wetlands (CWs). This study investigated four biochar-based vertical subsurface flow constructed wetlands (VSFCWs) (system I: intermittent aeration without biochar addition; system II: intermittent aeration with biochar addition; system III: tidal flow without biochar addition; system IV: tidal flow with biochar addition) to compare the effect of oxygen supply strategies on the performance and mechanism of nitrogen removal. The results showed that NH4 + N removal efficiencies were 85.83%, 87.88%, 96.19%, and 98.30% for systems I–IV respectively. The abundance of microbes involved in nitrogen transformation also increased in all VSFCWs, particularly in the tidal flow mode with biochar addition. The higher oxygen utilization rate and higher surface area provided by biochar could significantly improve microbial abundance and then enhance nitrogen removal. Most notably, the rate of nitritation (2.92, 3.82, 3.14 and 4.27 mg N L −1 h −1 ) was higher than that of nitration (0.51, 0.66, 0.83 and 0.89 mg N L −1 h −1 ) in systems I–IV, respectively, and the percentages of NO2 − -N denitrified via simultaneous nitrification denitrification (SND) in systems I–IV were 58.20%, 55.10%, 50.89% and 51.89%, respectively. Therefore, in addition to conventional nitrification denitrification, partial nitrification and SND via NO2 − -N were also the significant nitrogen transformation pathways in the four VSFCWs at high DO concentrations (2.43–6.84 mg L −1 ). These results demonstrated that the tidal flow biochar-based VSFCWs performed well in nitrogen removal due to efficient oxygen supplementation and enhanced microbial community abundance. Highlights: Intermittent aeration and tidal flow strategies markedly improved DO concentration. The tidal flow biochar-based VSFCW removed nitrogen most effectively. Partial nitrification and SND via nitrite were main nitrogen removal pathways.